rehabilitation Center for Disabled People - Asqalan, Ranad (My University, 2019)
As a center of the rehabilitation of people with special needs , especially disabled people , the idea of the project lies in providing a relaxing , recreational and social rehabilitation space , in which the user feels comfortable , safe and safety . As reflected in the design quality of the building , providing simplicity and strength ,because the design nature of such buildings is purely functional one. The building is designed in such a way that the movement inside the building is easy and simple , whether through the same floor or between the different floors . Therefore , the building is formed in semi-enclosed form for the possibility of free movement . The availability of stairs and elevators which lied in several places serves the same purpose . An external ramp has also been provided that will enable them to easily integrated with the external environment of the project . The glassed facades of the project were provided to give the maximum comfort to the users within the project . The glass is covered with vertical sunshaders to provide sufficient sunlight and to avoid harmful radiation. These facades will give an active environment full of energy which will encourage the users to achieve the different tasks .